2009
DOI: 10.1159/000230009
|View full text |Cite
|
Sign up to set email alerts
|

Severe Phenotype in a Girl with Partial Tetrasomy 7, Karyotype 46,XX,trp(7)(q35q36)

Abstract: On prenatal ultrasonography, polyhydramnion, internal hydrocephalus, hypoplasia of the corpus callosum, and dysmorphic features were detected in a fetus of a 22-year-old mother. Subsequent karyotyping of amniocytes revealed supernumerary material in distal 7q. The baby was delivered after 38+4 weeks of gestation, and postnatal array CGH analysis showed a triplication of 7q35→q36, resulting in partial tetrasomy. The triplication was not distinguishable from a duplication by conventional and molecular cytogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…Developmental delay and postnatal overgrowth might be suspected in case 2 because the 18.6 Mb supernumerary marker derived from chromosome 4 resulted in a partial segmental trisomy of over 65 genes including the IGFBP7 gene. The infant in our case has not shown any abnormality at age 1 year; and the trisomy segment is smaller than that reported by Bonnet et al For case 3, the compound effect from the 24.9 Mb deletion of 5p encompassing critical regions of speech delay, cat-like cry, MR, and facial dysmorphism of Cri du Chat syndrome [Zhang et al, 2005] and the 13.3 Mb 7q duplication [Lehnen et al, 2009] predicts a severe phenotype. The 6q27 deletion in case 4 includes the smallest deleted region and the proposed candidate gene TBP for MR [Rooms et al, 2006].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Developmental delay and postnatal overgrowth might be suspected in case 2 because the 18.6 Mb supernumerary marker derived from chromosome 4 resulted in a partial segmental trisomy of over 65 genes including the IGFBP7 gene. The infant in our case has not shown any abnormality at age 1 year; and the trisomy segment is smaller than that reported by Bonnet et al For case 3, the compound effect from the 24.9 Mb deletion of 5p encompassing critical regions of speech delay, cat-like cry, MR, and facial dysmorphism of Cri du Chat syndrome [Zhang et al, 2005] and the 13.3 Mb 7q duplication [Lehnen et al, 2009] predicts a severe phenotype. The 6q27 deletion in case 4 includes the smallest deleted region and the proposed candidate gene TBP for MR [Rooms et al, 2006].…”
Section: Discussioncontrasting
confidence: 53%
“…Case-oriented prenatal and follow-up postnatal genomic analyses have been used to further delineate prenatally detected chromosomal abnormalities [Baldwin et al, 2008; Lehnen et al, 2009; Rossi et al, 2009]. As demonstrated in this report, further characterization of gene copy number aberrations as opposed to chromosomal G-band abnormalities provides better predictive insight and, in turn, better patient management.…”
Section: Discussionmentioning
confidence: 99%
“…Bartsch et al 20 described independent small (550 kb) 7q36.3 microduplication and atypical 17q11.2 (NF1) microdeletion in a girl with neurofibromatosis and concluded that the 7q36.3 trisomy represented a subtelomeric CNV without phenotypic consequences. Lehnen et al 21 reported a severe phenotype in a girl with partial tetrasomy 7q35-q36. The only 7q36 duplication reported in the Decipher database (patient 254265, http://decipher.sanger.ac.uk/) in a subject with developmental delay, prominent eyes and short stature was inherited from her normal parents.…”
Section: Discussionmentioning
confidence: 99%
“…Partial trisomy 7q32.1q36.3 and 10q26.2q26.3 microdeletions were observed in Case 2 with the isolated ultrasound anomaly of hydrocephalus. Existing studies have suggested that partial trisomy or tetrasomy 7q may result in hydrocephalus 20 , 21 . Thus, we believe that the 7q32.1q36.3 duplication in this case may be the prime reason for the clinical feature of fetal hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%